Adolescents’ online communication and well-being: Findings from the 2018 health behavior in school-aged children (HBSC) study - Lyyra, Nelli; Junttila, Niina; Gustafsson, Jasmine; Lahti, Henri; Paakkari, Leena (Frontiers in Psychiatry, 2022)
Background: Digital transformation has influenced all areas of adolescents’ lives, including the ways adolescents maintain friendships. Interpersonal communication is one of the most common activities while online. Online communication may provide adolescents with opportunities to expand their social contacts, but these encounters can be risky, especially when the communication is with unknown people on the internet. This study examined the associations between different forms of online communication behavior and well-being. Methods: Data were collected from Finnish adolescents as part of the Health Behaviour in School-Aged Children (HBSC) study in 2018. The participants were 3140 Finnish adolescents aged 11 to 15 years. Descriptive analyses were used to examine the frequency of different forms of online communication behaviors. The associations between online communication and well-being indicators were analyzed using the Χ² test and 95% confidence intervals. Structural equation modeling (SEM) was used to analyze the extent to which adolescents’ online communication behavior explained the variance in adolescents’ well-being indicators. Results: Overall, 60% of the adolescents reported communicating intensively with close friends, with higher rates of intensive communication reported by girls, higher age groups, and the high health literacy group. 22% of adolescents reported intensive communication with friends they got to know through the internet (online friends), while intensive online communication with unknown people was reported by 13% of adolescents. Overall, around one-fourth of adolescents preferred sharing personal matters online rather than in face-to-face encounters, and 10% of adolescents reported using the internet daily to get to know new people, and to look for like-minded company. The SEM analysis showed that keeping online contact with offline friends was linked to a positive outcome in all the measured well-being indicators; however, intensive communication with people contacted only online (online friends and unknown people) was negatively associated with well-being indicators (lower self-rated health, lower life satisfaction, higher loneliness, and problematic social media use). Conclusions: Both positive and negative associations were observed between online communication and well-being, depending on the target and content of the communication. The results indicate that online communication has benefits for adolescents who have more offline social life.